Casrea Engineering Based on Extruded-Cassava-Urea as Protein Supplement for Slow Release of Ammonia in the Rumen In Vitro - Prasetiyono, BWHE; Suryahadi, Suryahadi; Toharmat, T; Syarief, R (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2008)
CASREA is protein supplement (PS) based on extruded-cassava-urea as main materials. The objective of this study was to examine the CASREA characteristics by evaluating ammonia concentration (NH3), Volatile fatty acids (VFA), rumen microbial protein synthesis (RMPS), and protein digestibility post rumen (PDPR). Variables of NH3, VFA and RMPS were analyzed with a completely randomized design in factorial (4X3), namely CASREA as factor A, consisted of: Casrea1 (made from 32% urea and 58% cassava without extrusion), Casrea2 (extrusion 22% urea and 68% cassava), Casrea3 (extrusion 27% urea and 63% cassava), and Casrea4 (extrusion 32% urea and 58% cassava), whereas the factor B was incubation times, consisted of 2, 4, and 6 hours incubation time. Variable of PDPR was analyzed with a completely randomized design, and the treatments were Casrea1, 2, 3, and 4. Results showed that there were no interactions between CASREA and incubation time on variables of NH3, VFA, and RMPS. Extrusion on CASREA materials reduced (P<0.05) NH3 and VFA, but increased (P<0.05) RMPS and PDPR. The highest RMPS and PDPR were 29.04 mg and 76.16%, respectively and were attained by Casrea2. Casrea1 had the highest NH3 (43.42 mM), whereas Casrea2 had the lowest (29.65 mM). Meanwhile, NH3 caused by Casrea2, Casrea3, and Casrea4 was 29.65, 30.54 and 31.44 mM, respectively and the increase these values were not significantly different. The concentration of NH3, VFA, and RMPS were stable on 4 hours incubation time. The present findings suggest that CASREA made from extrusion of 22% urea and 68% cassava as main materials was PS for slow release of ammonia (SRA) in the rumen due to reduction of NH3, but it improved the utilization of nitrogen for rumen microbial protein synthesis. (Animal Production 10(1): 34-41 (2008) Key Words: Extruded-cassava-urea, protein supplement, slow release of ammonia